Business Education Reformation Through Innovative Funding in Nigeria - Bintu Bolarinwa, Fehintola Fatimoh; Sofolahan, Victoria O. (Universitas Medan Area, 2025)
The study investigated Business Education reformation through innovative funding in Nigeria. It is an expository research design using secondary data. Recently, the discussion on the economy has brought the government's attention to the Business Education program in the Nation's educational system to combat unemployment and poverty in society and improve the Nation's economic performance. The system put in place by the Federal Government of Nigeria is to allow all sectors of the economy, including education, the need for the change of vocational training education, and the introduction of new strategies for its funding in the country. In this study, we learn and understand how to reform Business Education with proper funding in Nigeria. The sector faces funding challenges that limit its ability to deliver the desired outcome. Findings revealed that the government was solely responsible for funding business education in the country, and the available funds were inadequate to achieve the desired goals. Suppose the desired reformation of business education is to be completed. In that case, a new funding process for business education must be adopted for all institutions and sections, as well as private and multinational companies. However, it was suggested that for the transformation of business education in the Nation, funding processes that are innovative, such as alum endowment funds, foreign aid, increase in government budgetary allocation, Non-Governmental Organizations contributions, and rule of law on industries and manufacturing companies to contribute to business education growth in Nigeria